MiR‐205 mediates adaptive resistance to MET inhibition via ERRFI1 targeting and raised EGFR signaling. Issue 9 (24th July 2018) - Migliore, Cristina; Morando, Elena; Ghiso, Elena; Anastasi, Sergio; Leoni, Vera P; Apicella, Maria; Cora', Davide; Sapino, Anna; Pietrantonio, Filippo; De Braud, Filippo; Columbano, Amedeo; Segatto, Oreste; et al.
Abstract: The onset of secondary resistance represents a major limitation to long‐term efficacy of target therapies in cancer patients. Thus, the identification of mechanisms mediating secondary resistance is the key to the rational design of therapeutic strategies for resistant patients. MiRNA profiling combined with RNA‐Seq in MET‐addicted cancer cell lines led us to identify the miR‐205/ERRFI1 (ERBB receptor feedback inhibitor‐1) axis as a novel mediator of resistance to MET tyrosine kinase inhibitors (TKIs). In cells resistant to MET‐TKIs, epigenetically induced miR‐205 expression determined the downregulation of ERRFI1 which, in turn, caused EGFR activation, sustaining resistance to MET‐TKIs. Anti‐miR‐205 transduction reverted crizotinib resistance in vivo, while miR‐205 over‐expression rendered wt cells refractory to TKI treatment. Importantly, in the absence of EGFR genetic alterations, miR‐205/ERRFI1‐driven EGFR activation rendered MET‐TKI‐resistant cells sensitive to combined MET/EGFR inhibition. As a proof of concept of the clinical relevance of this new mechanism of adaptive resistance, we report that a patient with a MET ‐amplified lung adenocarcinoma displayed deregulation of the miR‐205/ERRFI1 axis in concomitance with onset of clinical resistance to anti‐MET therapy. Synopsis: Currently, one of the main challenges associated to targeted therapies is the almost inevitable occurrence of resistance. Thus, the identification of predictive biomarkers of resistance and the understanding of the resistance mechanisms are mandatory to improve the efficacy of these therapies. An actionable mechanism of resistance not relying on genomic alterations was identified. EGFR activation in MET‐addicted tumors is due to decreased ERRFI1 expression, caused by miR‐205 up‐regulation. Adaptive resistance can be overcome by combined blockade of MET and EGFR. Abstract : Currently, one of the main challenges associated to targeted therapies is the almost inevitable occurrence of resistance. Thus, the identification of predictive biomarkers of resistance and the understanding of the resistance mechanisms are mandatory to improve the efficacy of these therapies.